3(x+2)-(x-3)=15

Simple and best practice solution for 3(x+2)-(x-3)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-(x-3)=15 equation:


Simplifying
3(x + 2) + -1(x + -3) = 15

Reorder the terms:
3(2 + x) + -1(x + -3) = 15
(2 * 3 + x * 3) + -1(x + -3) = 15
(6 + 3x) + -1(x + -3) = 15

Reorder the terms:
6 + 3x + -1(-3 + x) = 15
6 + 3x + (-3 * -1 + x * -1) = 15
6 + 3x + (3 + -1x) = 15

Reorder the terms:
6 + 3 + 3x + -1x = 15

Combine like terms: 6 + 3 = 9
9 + 3x + -1x = 15

Combine like terms: 3x + -1x = 2x
9 + 2x = 15

Solving
9 + 2x = 15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 2x = 15 + -9

Combine like terms: 9 + -9 = 0
0 + 2x = 15 + -9
2x = 15 + -9

Combine like terms: 15 + -9 = 6
2x = 6

Divide each side by '2'.
x = 3

Simplifying
x = 3

See similar equations:

| x+1+x+2-x+3=0 | | -2(u-3)(u+9)=0 | | 3x+5y-6= | | y=ln(7*x) | | -20x+10y-35= | | -9(v+4)+3v+7=6v+9 | | 3d-27+18= | | (3+y)(5y-7)=0 | | y=ln(7*y) | | 3w+9=16+w | | -4m-24= | | 2x^2+ax+b=0 | | 3u(u-8)(u-7)=0 | | -(c-3)=-2 | | F(x)=4x-3x | | 20+0.05x=10+0.07x | | 6x+4-2(x+1)=9x+6 | | 6(3s+8)=264 | | 9-9Ln(x+8)=-27 | | 5(2l+5)=65 | | 6x-3y-4=0 | | 5(d-6)+8= | | 3(a-8)=27 | | 4x+6y+3x-y= | | (1-3x)(5x+2)=0 | | (u+4)*10=60 | | 14a+14b+4c+3c-6b-4a= | | (q-5)*5=15 | | 7x-6x=4x | | 5y+2=y+2 | | (e+2)*6=30 | | 15p+15q+p-6q-5p= |

Equations solver categories